Reducing anger outbursts after a severe TBI: a single-case study - Rochat, Lucien; Manolov, Rumen; Aboulafia-Brakha, Tatiana; Berner-Burkard, Christina; Van der Linden, Martial (Neuropsychological rehabilitation, 2019)
Anger outbursts constitute a frequent behavioural issue after a traumatic brain injury (TBI) and have a strong negative impact on the social outcomes resulting from the TBI. However, few studies have examined the efficacy of specific intervention strategies to reduce the frequency and intensity of anger outbursts. We therefore performed a single-case study on this topic by administering two successive and complementary psychological interventions with an AB design with maintenance (first intervention) and an AC design with maintenance plus a one-month follow-up (second intervention) to a patient with a severe TBI. Whereas the first intervention focused on improving the recognition and expression of basic emotions, the second consisted of a self-regulation programme, including various features such as psychoeducation about self-control strategies, relaxation and assertiveness training that aimed to establish adequate behaviours, which were further promoted by an implementation intentions strategy in the patient's daily life. The results indicated that all interventions resulted in a reduced frequency and intensity of anger outbursts, and the data upheld the specificity of these effects. In addition, a meta-analytic integration of the effects of both interventions on the outcomes indicated a medium effect size. Further research is needed on other patients who experience long-standing anger outbursts to examine whether the observed gains can be replicated, sustained on a longer-term basis and improved.